Aplikasi Informasi Hotel Rantauprapat Berbasis Android - Ike Yolanda (Universitas Labuhanbatu, 2021)
In an increasingly advanced ERA and rapid technological developments such as today, technology designed according to the needs and designed to be able to control a variety of jobs that can certainly process the information needed. The purpose of the study is to be able to design an Android-based Rantauprapat Hotel Information application so that it can provide accurate information, especially in about the hotel. Hotel as a container or place to rest when we are traveling far or are traveling between in town or out of town. The same is the case with the increasing number of large buildings in various big cities.